Special Education and At-Risk Kindergarteners as Authors - Kramer-Vida, Louisa; Levitt, Roberta; Kelly, Susan P. (Journal of the American Academy of Special Education Professionals, 2010)
Special Education and at-risk kindergarteners can be outstanding authors given the appropriate educational opportunity. In a small, suburban public school district, two university professors collaboratively met with experienced special and general education teachers to introduce them to writing workshop methodology. This year-long series of monthly meetings and in-class demonstrations by the consultants supported the kindergarten educators as they taught writing to all children. The special and general education teachers shifted from an emphasis on student products to focusing on children’s abilities and needs as the kindergarteners composed their pieces during writing workshop. According to the teachers, student work "far exceeded their expectations." Pictures of youngsters’ compositions, samples of topics used, and some teacher developed tools are included in this article to show that writing workshop was a positive experience for all. The workshop approach motivated the children to see themselves as authors and honored everyone’s attempts and accomplishments.